3x^2 -14x +15 = (3x-5)(x-3)
14x squared minus 7x to the 3rd power can be factored to 7x2(2-x).
7x2 - 14x = 7x(x - 2)
3x2 -14x -24 can be factored as (3x + 4)(x - 6).
21x3-35x2+14x = 7x(3x2-5x+2)
14x2-7x2-16 7x2-16 (this can't be simplified any more)
14x2 - 39x - 35 = (7x + 5)(2x - 7)
I suppose that would be 14x2 - 7x3. Just take out the common factor, 7x2. Divide each term by this factor to find the other factor.
7(x - 1)(x + 3)
(x - 16)(x + 2) x = 16 or -2
Yes because if x2-14x+49 then it is (x-7)(x-7) when factored
(2x + 5)(7x - 3)
(4x + 1)(2x + 3)
The polynomial IS written in descending order.
14x(x + 2)
5x2 + 14x - 3 let 14x = 15x - x=5x 2 + 15x - x - 3 factor out 5x and -1 = 5x(x + 3) - 1(x + 3) factor (x + 3) = (x + 3)(5x - 1)
if its x(squared) its 7x(cubed) if its 2xX its 14x(squared)
23x - 9x = 14x
yes, and it is 14x